2017
DOI: 10.1373/clinchem.2016.254680
|View full text |Cite
|
Sign up to set email alerts
|

Counterpoint: Potential Concerns Regarding the Use of Sex-Specific Cutpoints for High-Sensitivity Troponin Assays

Abstract: There are biological differences between males and females in cardiac structure and function that have been recently revealed using sensitive imaging techniques such as magnetic resonance tomography (1 ). With the availability of more sensitive assays capable of measuring extremely low concentrations of cardiac troponin, such biological differences may contribute to 99th percentile reference values for cardiac troponin that have been found to be lower in women than in men (2 ). Although it is still unclear whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…However, the current clinical evidence supporting the use of sex-specific thresholds are controversial 30 33 . There are relevant concerns regarding the use of sex-specific thresholds 34 , 35 . It is also conceivable that the clinical decision limits for myocardial infarction in different assays are not biologically equivalent 36 .…”
Section: Discussionmentioning
confidence: 99%
“…However, the current clinical evidence supporting the use of sex-specific thresholds are controversial 30 33 . There are relevant concerns regarding the use of sex-specific thresholds 34 , 35 . It is also conceivable that the clinical decision limits for myocardial infarction in different assays are not biologically equivalent 36 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has shown that sex-specific cut-offs for ruling in MI increase classification performance by increasing the specificity of the assay. [7][8][9][10] We hypothesized, based on these findings, that similar improvements in classification performance would be observed for sexspecific, rule-out cut-off concentrations, with minimal loss of sensitivity. This would potentially enable more patients to have MI ruled out with a single hs-cTnT measurement compared to currently recommended universal rule-out cut-off concentrations.…”
Section: Discussionmentioning
confidence: 93%
“…6 Sex-specific diagnostic cut-offs for high-sensitivity troponin assays have been proposed for ruling-in MI. [7][8][9][10] In the rule-in scenario, sex-specific cut-offs improve diagnostic specificity and classification performance. [7][8][9][10] We hypothesized that sex-specific rule-out cut-offs would improve the classification performance of a single hs-cTnT measurement performed at ED arrival for rapidly ruling out MI with negligible loss of sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…As detailed in the counterpoint argument by Giannitsis, the adoption of ruling in MI with sex-specific cut off values in previous studies has shown very little clinical benefit. 9 The use of reclassification should be with caution due to inherent confirmation bias, as the troponin values are incorporated in the adjudication of MI outcome in these studies. Future studies are needed to confirm that sex-specific cut-offs improve the diagnosis of MI and specifically the impact on clinically important hard outcomes such as mortality, and revascularization procedures should be documented.…”
Section: Introductionmentioning
confidence: 99%